Efektifitas Bimbingan Pra Nikah dan Tingkat Perceraian di Kota Lhokseumawe - Siti Hanifa (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2025)
This study aims to explore and analyze the effectiveness of premarital counseling at four Religious Affairs Offices (KUA) in Lhokseumawe City, Blang Mangat, Muara Satu, Banda Sakti, and Muara Dua, and its relevance to divorce rates in each area. Although premarital counseling is designed as a preventive effort to equip future spouses with the skills to build harmonious families, divorce rates remain high, raising questions about the program’s substantive effectiveness. Using an empirical legal approach with descriptive qualitative methods, data were collected through interviews, documentation, and marriage-divorce records from 2023–2024. The findings reveal that despite formal compliance with regulations, the program remains ineffective due to limited session time, superficial material, and the absence of continuous evaluation and post-marital guidance. Notably, digital innovations such as the use of online platforms at Muara Dua KUA have not yielded a measurable reduction in divorce rates, highlighting a gap between administrative innovation and substantive behavioral outcomes. The novelty of this research lies in revealing that technological integration alone does not enhance program effectiveness without psychological, communicative, and evaluative reinforcement mechanisms. The study recommends strengthening facilitator training, implementing long-term evaluation systems, and fostering cross-sectoral collaboration to transform premarital counseling from a procedural requirement into a substantive preventive instrument for family resilience.